Urgency of Changing the Notary Law as a Form of Legal Protection for Notaries and Their Clients - Aqil, Muhammad Zumri; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract.This study aims to analyze: 1) The legal force of the Notary Law in providing legal protection for notaries and their clients at this time. 2) The form of change needed so that the Notary Law is more optimal in protecting notaries and their clients. This type of research is included in the scope of normative legal researcp. This type of research is normative legal researcp. The approach method in this study is the Legislation approach (statue approach). The type of data in this study is secondary data sourced from primary, secondary and tertiary legal materials. The data collection method uses library techniques (study documents). The analysis in this study is prescriptive. The results of the study concluded: 1) The legal force of the Notary Law in providing legal protection for notaries and their clients at this time, namely Protection for notaries is reflected in the regulation of authority in Article 15, the summons mechanism in Article 66, and supervision through the Notary Supervisory Board as regulated in Articles 67–81. Meanwhile, clients receive legal guarantees through Article 16 which affirms the independence of notaries, Article 54 which regulates the confidentiality of deeds, and Articles 84–85 which give clients the right to claim compensation in the event of a violation. 2) The form of change needed so that the Notary Law is more optimal in protecting notaries and their clients, namely one change needed is strengthening the mechanism for summoning notaries by law enforcement officers in Article 66, by setting a time limit for the Notary Honorary Council (MKN) to provide approval to prevent potential abuse of authority. In addition, Article 15 needs to be updated to accommodate the legality of electronic deeds, so that notaries can adapt to technological developments and provide more efficient services. In order to ensure transparency and certainty for clients, Article 16 must regulate the obligation of notaries to include a list of official fees, so as to prevent illegal levies that can harm users of notary services. In terms of law enforcement, Article 85 needs to be strengthened with stricter sanctions, such as the implementation of administrative fines and a blacklist system for notaries who are proven to have committed serious violations. Keywords: Client; Legal Protection, Notary; UUJN.